2011
DOI: 10.1371/journal.pone.0028026
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Chronic Wasting Disease Identifies a Prion Strain Causing Cachexia and Heart Infection in Hamsters

Abstract: Chronic wasting disease (CWD) is an emerging prion disease of free-ranging and captive cervids in North America. In this study we established a rodent model for CWD in Syrian golden hamsters that resemble key features of the disease in cervids including cachexia and infection of cardiac muscle. Following one to three serial passages of CWD from white-tailed deer into transgenic mice expressing the hamster prion protein gene, CWD was subsequently passaged into Syrian golden hamsters. In one passage line there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 81 publications
1
17
2
Order By: Relevance
“…Table 1 summarizes the transmission studies of CWD into HPrP7752KO mice and SGH. A portion of this table appeared in a previous publication and is included here in order to present the transmission history of the wasted (WST) strain of CWD (previously called CWD line A) and CWD line B, now identified as the cheeky (CKY) strain of CWD (40). The new animal transmission data includes second and third serial passages of CKY CWD and WST CWD in SGH, respectively, and serial backpassage of each into HPrP7752KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the transmission studies of CWD into HPrP7752KO mice and SGH. A portion of this table appeared in a previous publication and is included here in order to present the transmission history of the wasted (WST) strain of CWD (previously called CWD line A) and CWD line B, now identified as the cheeky (CKY) strain of CWD (40). The new animal transmission data includes second and third serial passages of CKY CWD and WST CWD in SGH, respectively, and serial backpassage of each into HPrP7752KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…For biochemical tissue analysis, tissues were collected, immediately frozen over dry ice, and stored at Ϫ80°C until use. For collection of tissues for immunohistochemistry, hamsters were intracardially perfused with periodatelysine-paraformaldehyde fixative, and tissues were dissected and processed for embedding in paraffin wax as previously described (39)(40)(41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data raised the possibility not only that PrP Sc might be deposited in the heart of individuals with prion disease but also that abnormal forms of PrP could be an unrecognized component of amyloid heart disease in humans (19). Consistent with this possibility, PrP Sc has been reported in the heart of one sCJD patient (20), in muscle tissue (including heart) of BSEinfected nonhuman primates (21), in a BSE-infected macaque with a prion-amyloid cardiomyopathy (22), and in several chronic wasting disease models (23,24). In contrast, several studies have failed to detect PrP Sc in either sCJD heart tissue (9,12,19) or human amyloid hearts (19), and heart tissue from several sCJD patients did not transmit disease to nonhuman primates (25).…”
mentioning
confidence: 84%
“…Recently, using a model of transgenic mice overexpressing mule deer prion, the possibility of at least two CWD strains existing in North American cervids was raised [1]. More evidence on the two distinct CWD strains that originated from the mule deer was suggested using the ferret model [9] and from Syrian hamster model studies, and the emergence of a new "wasting strain" (WST) would appear to have occurred in white-tailed deer [2]. Epidemiological investigations showed that CWD was introduced to the Korean peninsula via importation of infected elk from Canada in 1994, 1995 and 1997 [7].…”
mentioning
confidence: 99%